Contribution of Artificial Intelligence (AI) in Education to Support the Achievement of Sustainable Development Goals (SDGs) 2030 - Diah Arini; Muhammad Nursa’ban (Postgraduate, University of Mataram, 2024)
This research aims to find out the contributions and threats of AI in education so that it can contribute to technological development in the SDGs 2030 era. The method in this research is qualitative using literature study. The contributions of AI in education include personal virtual tutors, adaptive learning systems, learning Chabot, game-based learning, AI based assessment systems, educational data analysis, automatic evaluation, accessibility and inclusiveness, assistants for learning, and helping to develop curriculum. The contribution of AI in education is very helpful for students to improve their skills and knowledge. It is expected that more will be able to participate in SDGs 4 (Quality Education). Threats of AI in education include data privacy and security, technology gaps, dependence on technology, fraud, and algorithm imperfections. Thus, there should be collaboration with AI experts to develop strategies and data simulations to minimize the threats.